Efficient lottery design - Onur Kesten; Morimitsu Kurino; Alexander Nesterov (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
There has been a surge of interest in stochastic assignment mechanisms which proved to be theoretically compelling thanks to their prominent welfare properties. Contrary to stochastic mechanisms, however, lottery mechanisms are commonly used for indivisible good allocation in real-life. To help facilitate the design of practical lottery mechanisms, we provide new tools for obtaining stochastic improvements in lotteries. As applications, we propose lottery mechanisms that improve upon the widely-used random serial dictatorship mechanism and a lottery representation of its competitor, the probabilistic serial mechanism. The tools we provide here can be useful in developing welfare-enhanced new lottery mechanisms for practical applications such as school choice.
Keywords: C71; C78; D71; D78; 330; lottery; ex post efficiency; sd-efficiency; random serial dictatorship